2022
DOI: 10.1108/ijbm-05-2022-0185
|View full text |Cite
|
Sign up to set email alerts
|

Financial capability: a systematic conceptual review, extension and synthesis

Abstract: PurposeThis study aims to examine the literature on consumer financial capability. By analyzing the research trends, theories, definitions and themes, the literature on financial capability is synthesized, and agenda for future research is suggested. A framework is presented that portrays the antecedents as well as the outcomes of financial capability and their interlinkages.Design/methodology/approachFollowing a systematic approach, the review is based on 215 articles published during January 2007 and–March 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 214 publications
2
25
0
Order By: Relevance
“…However, our higher FKB score for single mothers agrees with West and Mitchell (2021), who showed that women with sound financial knowledge have better wealth outcomes in divorce. Findings from this study strengthen the findings of Xiao et al . (2022), who conceptualized financial capability using financial knowledge, behavior and opportunity.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, our higher FKB score for single mothers agrees with West and Mitchell (2021), who showed that women with sound financial knowledge have better wealth outcomes in divorce. Findings from this study strengthen the findings of Xiao et al . (2022), who conceptualized financial capability using financial knowledge, behavior and opportunity.…”
Section: Discussionsupporting
confidence: 91%
“…However, our higher FKB score for single mothers agrees with West and Mitchell (2021), who showed that women with sound financial knowledge have better wealth outcomes in divorce. Findings from this study strengthen the findings of Xiao et al (2022), who conceptualized financial capability using financial knowledge, behavior and opportunity. The findings of correlation analysis in terms of age agree with those of Kunaifi et al (2019), who found that younger millennials tend to invest more, and their financial resilience is more than that of older millennials.…”
Section: Cognitive Abilities and Financial Resiliencesupporting
confidence: 82%
“…The concept of digital financial capability is gaining traction amongst policymakers as a response to the growing importance of digitalisation and the need for informed financial decision-making (Xiao et al. , 2022).…”
Section: Methodsmentioning
confidence: 99%
“…An inevitable overlap in terms of financial literacy and financial capability usage as part of financial inclusion has been observed. In their systematic literature review, Xiao et al. (2022) present the five main kinds of financial capability, which signifies an individual's capacity to apply proper financial knowledge and suitable financial behaviour and grab important financial opportunities for financial well-being.…”
Section: Review Of Earlier Studies and Hypotheses Developmentmentioning
confidence: 99%
“…, 2007; Lusardi and Mitchell, 2007; Taylor, 2011; Xiao et al. , 2014; Also see a review by Xiao et al. , 2022).…”
Section: Literature Reviewmentioning
confidence: 99%